A conceptual integrated health information systems framework in postnatal care for modern and traditional malay medicine - Raja Rina Raja Ikram; Lizawati Salahuddin; Mohd Hariz Mohd Naim; Ariff Idris; Nor Afirdaus Zainal Abidin; Nadiah Ishak; Noor Raihan Ab Hamid (Institute of Advanced Engineering and Science, 2020)
This paper proposes an integrated health information systems framework for Traditional Malay Medicine (TMM) and modern medicine in the field of postnatal care. A qualitative study was conducted via healthcare experts in the field of modern medicine and Traditional Malay Medicine to assess the current situation and identify the research gap and point of isolation between both traditional and modern medicine field. A total of 26 healthcare practitioners whom represented five different set of healthcare organisations participated in this study. The healthcare practitioners consist of modern and traditional Malay medicine background with and without proper training. Results show that there is a gap in the current people, process and technology areas of the current framework. A novel conceptual framework, MyPostnatal, proposes the existence of a sufficiently generic, extensible in-formation model where new data sources can be integrated without major changes to the data scheme. Human and organization factors are also highlighted to stimulate the adoption towards electronic health records.